Emotional intelligence as a contributor to enhancing educators’ quality of life in the COVID-19 era - Maharaj, Prashanti; Ramsaroop, Anisha (Frontiers in Psychology, 2022)
The basic education fraternity is constantly evolving with various stressors amongst others, curricular changes, adaptation to the Fourth Industrial Revolution, poor educator development, excessive workload, and brain drain, thus negatively affecting educators’ quality of life. The Coronavirus (Covid-19) has expedited the importance of emotional intelligence, as an essential resilience skill for enhancing the quality of life during adversity. The objective of the study is to ascertain the relationship between emotional intelligence and the quality of life of educators. A quantitative approach was utilised using simple random sampling. A sample of 108 educators from a population of 154 was drawn from 6 schools in the Reservoir Hills precinct of KwaZulu-Natal. The findings revealed a significant relationship between emotional intelligence and the quality of life of educators. A practical research model was advocated for key stakeholders in the South African basic education sector.